L'educazione alla democrazia intelligente dello sviluppo locale attraverso i Circoli di Studio - Paolo Orefice (Firenze University Press, 2017)
The essay is focused on the theoretical and methodological model of education at the bases of Study Circle in the framework of decentralized system of sustainable and endogenous Local Development. The aims is to underline those SC components required to contribute to the creation of a lifelong open knowledge in local community based on equity, solidarity, and well-being of the territory and its inhabitants of today and tomottow: this is the education of citizens to the democracy of emancipated intelligence. The sustainability of SC consistes in the possibility of learning process to interact with the context and the contents of knowledge, with personal feeling and thinking to interpret and to transform in the same time the subject and context. One of the SC educational methodologies that supports and implement the theory of complex knowledge in order to ensure sustainable development is the Participatory Action Research. The phases and the integrated flow of PAR are defined in the context of SC.